Fear and tolerance to frustration in students - Alberca-Lonzoy, Carmen Noemi; Fernández-Calizaya, Miguel Ángel; Alberca-Lonzoy, Ana Lourdes (Horizonte Sanitario, 2024)
Objective: Determine the relationship between fear of contagion by COVID-19 and frustration tolerance in secondary school students returning to in-person classes.Materials and methods: quantitative, cross-sectional and correlational design study. The study population consisted of 642 adolescents and the Fear of COVID-19 Scale (FCV-19S) and the Frustration Tolerance Scale for Adolescents (TFA) were used to collect data.Results: It was obtained as soon as to the fear variable, 55% had a medium level, 26.5% had a low level and 18.5% had a high level; Regarding frustration tolerance, 48.1% presented a medium level, 26.9% a low level and 24.9% a high level; When performing the Spearman Rho test to determine their correlation, it was found that there is no relationship between both variables in the population studied, since significance values ​​>0.05 were obtained.Conclusion: The null hypothesis is accepted, there is no relationship between fear and frustration tolerance in secondary school students. Descriptors: Fear; Tolerance; Frustration; Teenagers.